SELETIVIDADE DO HERBICIDA ATRAZINE EM ESPÉCIES DE CROTALÁRIA - Timossi, Paulo César (2024)
One of the limitations of adopting crotalaria in crop rotation is the lack of information on the selectivity of herbicides for controlling volunteer soybean plants. To find alternatives for soybean management, the selectivity of atrazine applied pre-emergently to crotalaria species at a dose of 2.5 kg ha-1 of atrazine active ingredient was investigated. The experiment was set up in the experimental area of the Federal University of Jataí, using a randomized block design arranged in a 3x3+1 factorial scheme consisting of three species of crotalaria (Crotalaria juncea, C. spectabilis, and C. breviflora), three periods of application of the herbicide atrazine (20, 10, and 0 days before sowing) and a control treatment (no application of atrazine) with four replications. The density of emerged crotalaria plants 10 days after sowing was assessed. Plant height and fresh and dry biomass were assessed at 30, 60, and 90 days. It can be concluded that the application of atrazine at 0 DAS interferes with the initial development of Crotalaria juncea, and the species Crotalaria spectabilis and Crotalaria breviflora do not show any interference in the establishment and development of the plants when grown in clay soil.